2005
DOI: 10.1016/j.ijindorg.2005.08.006
|View full text |Cite
|
Sign up to set email alerts
|

An econometric analysis of the European Commission's merger decisions

Abstract: Using a sample of 96 mergers notified to the European Commission and logit regression techniques, we analyse the Commission's decision process. We find that the probability of a phase-2 investigation and of a prohibition of the merger increases with the parties' market shares. The probabilities increase also when the Commission finds high entry barriers or that the post-merger market structure is conducive to collusion. We do not find significant effects of bpoliticalQ variables, such as the nationality of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
88
0
3

Year Published

2006
2006
2015
2015

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 90 publications
(105 citation statements)
references
References 19 publications
9
88
0
3
Order By: Relevance
“…Considering a sample of 167 EU mergers between 1990 and 2002, they find that the Commission's decisions are not solely guided by the motive of protecting consumer surplus but also driven by the institutional and political environment. Bergman et al (2005) provide an econometric investigation of 96 mergers investigated by the European Commission before 2002. Applying logit models, the authors find that the probability of a Phase II investigation (and of a prohibition of the merger) increases with the parties' market shares, the presence of high entry barriers and a collusion-friendly post-merger market structure.…”
Section: Review Of Related Literaturementioning
confidence: 99%
See 1 more Smart Citation
“…Considering a sample of 167 EU mergers between 1990 and 2002, they find that the Commission's decisions are not solely guided by the motive of protecting consumer surplus but also driven by the institutional and political environment. Bergman et al (2005) provide an econometric investigation of 96 mergers investigated by the European Commission before 2002. Applying logit models, the authors find that the probability of a Phase II investigation (and of a prohibition of the merger) increases with the parties' market shares, the presence of high entry barriers and a collusion-friendly post-merger market structure.…”
Section: Review Of Related Literaturementioning
confidence: 99%
“…Alongside the authority-and case-related determinants, market-related determinants constitute a third subset of variables that possibly influence the duration of Phase II investigations in particular, however variables such as 'premerger HHI', 'combined market share of the merging parties', 'delta HHI post-merger' or 'high entry barriers' by definition relate to the characteristics of specific relevant markets within the merger case under investigation (see also Bergman et al (2005)). As most investigated mergers affect more than one relevant market, the variables in this setting could only refer to, for example, the relevant market in the respective investigation in which competition concerns were the greatest, however such an approach would ignore the situation in all remaining relevant markets and therefore appears problematic as a potential driver of the speed of Phase II investigations.…”
Section: Case-related Determinantsmentioning
confidence: 99%
“…There is also another strand of the economic literature on ex post evaluations by competition authorities, which focus on merger clearance decisions, and decisions on abusive and concerted practices (e.g. Khemani and Shapiro (1993), Davies, Nigel & Clarke (1999), Bergman, Jakobsson & Razo (2005Carree, Guenster & Schinkel (2010, Gual and Mas (2011)). However, the data generating process for our sample of multilateral practices is unique, and it is different from the data generating process for an authority detecting anti-competitive behavior or the data generating process for leniency or merger clearance applications.…”
Section: Individual Exemptions and Their Economic Effects: A Brief Rementioning
confidence: 99%
“…3 The European report suggested that merger remedies had permitted more concentrations to be accepted but highlighted a series of flaws in their design and implementation. 4 The analysis was based on interviews with merging parties, competitors and trustees. Moreover, the European agency has to face recent questioning about the validity of its merger control.…”
Section: Introductionmentioning
confidence: 99%
“…In order to estimate the relationship between merger remedy decisions and market 4 For instance, the scope of the divested business, the viability of the purchaser, and strategic behaviors between sellers and purchasers can raise serious concerns about the efficiency of some remedies. 5 The famous Airtours/First Choice, TetraLaval/Sidel and Schneider/Legrand merger cases.…”
Section: Introductionmentioning
confidence: 99%